PROBLEMATIKA DAN SOLUSI DALAM PEMBELAJARAN DI SEKOLAH DASAR PADA MASA PANDEMI COVID-19 - Elmania Nur Farida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The COVID-19 pandemic has significantly impacted various sectors of life, including basic education. The transition from face-to-face learning to distance learning (DL) has brought about numerous challenges, especially at the elementary school level where students highly depend on direct guidance. This study aims to identify the problems and solutions that emerged in elementary school learning during the pandemic. This research employs a qualitative approach using a literature review method. Data were obtained from various scientific articles, national journals, and relevant research reports published within the last five years. The data were analyzed descriptively by grouping them into key thematic categories. The results show that the main problems faced in elementary school learning during the COVID- 19 pandemic include: (1) limited technology and infrastructure, (2) lack of digital competence among teachers and students, (3) low parental support and involvement, (4) decreased student motivation and independence, (5) limited interaction and learning approach, and (6) difficulty in assessment and learning supervision. The identified solutions include the use of simple and accessible learning media, digital literacy training for teachers, strengthening communication with parents, implementation of enjoyable and contextual learning methods, and the development of alternative assessment strategies. This study is expected to serve as a reference for teachers, schools, and policymakers in designing more adaptive learning strategies, and also as a foundation for further research on similar topics.